ENGLISH MEDIUM INSTRUCTION POLICY AND PRACTICE IN THE MULTILINGUAL CONTEXT OF A PRIVATE UNIVERSITY IN KAZAKHSTAN: A QUALITATIVE STUDY - Kazhigaliyeva, Aigerim (Nazarbayev University Graduate School of Education, 2024)
This thesis presents findings from a qualitative study conducted in one private university in the city of Astana to examine the English medium instruction policy and practice in the multilingual context of Kazakhstan. The study was conducted in response to the challenges the universities reportedly confront regarding the effective implementation of the English Medium Instruction (EMI) policy, a phenomenon that is relatively recent in the context of Kazakhstan. The focus of the study was to explore how different stakeholders (administrators, teachers, and students) understood the EMI policy, what challenges they confronted in its implementation, and the practices especially those of teachers as to how they manage and negotiate the policy within the classrooms in day-to-day transactions, and how their teaching and learning approaches accounted for the local languages and students’ multilingual repertoires. Employing a qualitative research design, the study used multiple data collection tools that included interviews, classroom observations, documents analysis, and other relevant sources such as informal conversations with different stakeholders during the fieldwork, fieldnotes, and an analysis of the linguistic landscape used within the research site. The findings of the study suggest that the stakeholders’ overall perspectives about the EMI are positive, thinking of EMI as a move forward towards the future of the country. EMI, in their view, will not only put Kazakhstan at an economic advantage, but it will also help Kazakhstani graduates to gain access to all forms of modern knowledge, and thus become globally competitive. The findings also suggest that brighter hopes and aspirations aside, the EMI policy still faces numerous challenges in the context. The main challenges include students’ low English proficiency, teachers’ language proficiency, teachers’ lack of professional development in the EMI, and the university’s overall preparedness level to meet the EMI demands in the form of the essential resources such as books, library, online-sources, and access to the internet. Other important findings suggest that teachers ideologically hold orthodox monoglossic orientations towards the use of the EMI policy in the classrooms, where they would ideally like to teach contents through English-only approach, because, as they believe, the use of the local languages may reduce the quality of an EMI policy. However, the practical challenges and the contextual linguistic realities make teachers take recourse to the multilingual resources of the students, because the idealized monoglossic notions of EMI conflict with students’ current English language proficiency and their readiness to cope with the challenges of the academic English. Thus, as a forced measure, teachers negotiate the challenges by their recourse to a linguistically flexible teaching approach, where they allow for translanguaging practices so that students can access contents easily and participate effectively in the classroom. Theoretically, the study concludes that language policy is a complex, dynamic, and multilayered phenomenon. It does not operate in a linear way, as it is typically understood as either top-down or bottom-up. Most importantly, the local actors such as students, teachers, and local administrator working at the micro-level perform more important agentive roles as arbiters and implementors of the policy. In the end, I recommend that the universities in a context such as Kazakhstan, need to not only realistically analyze the needs of the EMI policy, the professional development needs of teachers and students, but also re-envision the EMI policy within the local sociolinguistic landscape, facilitating a more localized form of EMI, where the local languages and local multilingualism is utilized as a pedagogical/instructional resource to effectively mediate the EMI policy, and thus reduce the degree of challenges the English language poses in the context. In policy terms, this would require both the management and EMI teachers to develop critical multilingual language awareness.
Keywords: EMI; language policy; language practice.; type of access: gated access